Social Skill in Problem Based Learning with Sociocultural Insight (Journal of Primary Education, 2020)
The research aim is to analyze the influence and effectiveness of problem based learning model with sociocultural insight to student social skill. This quasi experimental research used nonequivalent control group design. The sample consisted of Primary School I Krangkeng students as the experimental group and Primary School II Krangkeng as the control group. They were taken by purposive sampling technique. The technique of collecting data was questionnaire. Then, it was analyzed by Paired Sample t-test and Independent Sample t-test. The findings showed that problem based learning with sociocultural insight could improve the students’ social skills. It was proven by social skill average improvement from pretest – 34.17 into posttest – 43.76, there was significant difference between experimental group – implementing problem based learning with sociocultural insight, and control group – implementing expository or conventional model. It was shown by the significant score, lesser than 0.05. It was 0.005 > 0.05 and 0.003 > 0.05.